Criteria of evaluation of indicators of speed of movements at young men in rowing - Volodymyr Bogush; Sergiy Getmantsev; Olga Kuvaldina; Yuriy Kulakov; Olga Sokol; Yevgen Yatsunskiy (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to develop criteria of evaluation of indicators and components of physical quality of speed. Material & Methods: young men, who specialize in rowing, that differ on age and sports qualification, were examined. Sensomotory reactions to sound and light irritants were investigated, and rate, time and speed of one movement, frequency of movements were defined by the developed by us technique of measurement of effect of training action. The process of testing models typical conditions of training and competitive activity and estimates performance of task. Results: criteria of the assessment are developed for young men of different age and sports qualification, who go in for rowing on the basis of the conducted complex researches of indicators of physical quality of speed and elements making it (rate, time and speed of one movement, frequency of movements). The offered technique of researches allows studying force and mobility of nervous processes, functional endurance and psychomotor efficiency of sportsmen. Conclusions: the developed criteria of evaluation of physical quality of speed allow finding specific psychophysiological features of organism of the sportsman, which will give the chance to introduce amendments in the improvement of high-speed abilities and to operate the training process effectively.